PENGARUH PENERAPAN PROTOKOL KESEHATAN DAN PERSEPSI RISIKO TERHADAP KEPERCAYAAN WISATAWAN KE TAMAN REKREASI SELECTA, MALANG - Ilham, Muhammad Farhan; Dewi, LGLK.; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Selecta Recreation Park is one of the tourist recreational parks located in Batu City and is one of the tourist attractions that is able implement health protocols to provide comfort and health for tourists who want to visit in the midst of the ongoing pandemic. One of the things that becomes an important point during a pandemic when tourists visit tourist attractions is how they perceive the risks they face will generate trust from tourists in the tourist attractions they visit. This study aims to determine the effect of implementing health protocols on tourist trust with perceived risk as an intermediate variable. The research sample used in this study was domestic tourists who visited the Selecta recreational park with a total of 100 respondents. The data analysis technique is quantitative descriptive analysis using partial least squares (PLS) analysis to determine the effect of the independent variables on the dependent variable and the intermediate variables in it. The results obtained in this study show that the application of the CHSE health protocol has an effect the confidence of domestic tourists with a t-statistic value of 4.960 which is greater than the t-table (1.96) with a p-value of 0.000. Furthermore, the risk perception variable has an influence on trust with a t-statistic value of 2.057 which is greater than t-table (1.96) and a P-value of 0.003. on the effect of the risk perception variable on trust, the t-statistic value of 2.507 is greater than the t-table of 1.96 with a p-value of 0.013 which indicates that risk perception affects the confidence of domestic tourists who visit the Selecta recreation park. Furthermore, on the indirect effect between the CHSE health protocol on tourist trust, where the perception of risk as an intervening variable gets a t-statistic value of 1.985 which is greater than the t-table of 1.96 with a p-value of 0.048. These results indicate that the application of health protocols indirectly affects the confidence of domestic tourists with the perception of risk as an intervening variable.